Selective loss tailoring of broad-area diode lasers. (19th January 2021) - Su, Jiaxin; Tong, Cunzhu; Wang, Lijie; Wang, Yanjing; Lu, Huanyu; Wang, Jun; Tan, Shaoyang; Li, Sensen; Peng, Hangyu; Wang, Lijun
Abstract: High-power high-brightness broad-area diode lasers have poor lateral beam quality, which has limited the application range of this kind of device. To improve the lateral beam quality, a sawtooth microstructure laser was proposed and the microstructures were carefully designed according to the profiles of each lateral mode and their dependence on the self-heating induced thermal lens effect. As a result of selective mode loss adjustment, a 42% improvement in lateral beam quality was achieved under the power-maintained condition. This technology enables us to develop high-brightness direct-diode laser systems.